Buying better biosecurity: Plant‐buying behaviour and the implications for an accreditation scheme in the horticultural sector. Issue 3 (26th December 2019) - Dunn, Mike; Marzano, Mariella; Forster, Jack
Societal Impact Statement: The horticultural trade relies on healthy plants to flourish. However, its very nature means that it is also a key pathway for the introduction and spread of plant pests and diseases. These pests and diseases threaten horticultural stakeholders, and can also cause huge ecological and economic damage. A horticultural sector accreditation scheme, underpinned by best biosecurity practice, could help reduce these threats. Drawing on survey responses, this study examines the plant‐buying habits of UK consumers and their appetite for a horticulture accreditation scheme. We consider the necessary scope of such a scheme and outline how it could be made appealing to the plant‐buying public. Summary Movement of live plant material through the horticultural trade is a recurrent pathway for the introduction and spread of pests and diseases. An accreditation scheme underpinned by best biosecurity practice represents one approach to mitigating this risk. This research aims to determine whether an accreditation scheme would likely be supported by the public in the United Kingdom—a factor which would heavily influence its establishment and impact. Consumer attitudes and behaviours were elicited through a survey of the UK's plant‐buying public ( n  = 1, 500). The survey explored awareness of pests and diseases, the importance of biosecurity when making plant‐buying decisions (relative to other factors), and appetite for accredited products, including plants. The sample exhibited limited awareness of plant pests and diseases and ascribed little importance to biosecurity during plant‐buying decisions. Instead, these decisions are influenced by "quality"—a factor also cited to explain consumers' selection of (non‐horticultural) accredited goods over unaccredited varieties. Despite apparent support of a horticultural accreditation scheme's ideals, consumers expressed concern that accreditation could lead to more expensive products. Public support for a scheme aiming to safeguard the wider environment from pests and diseases is unlikely to materialize without dedicated efforts to raise awareness by key influencers such as retailers. However, an assurance of high‐quality, healthy plants would increase a scheme's appeal. Furthermore, given the diversity of sources from which plants are obtained, any would‐be scheme must encompass a range of growers and sellers if it is to be widely considered by the plant‐buying public. Abstract : The horticultural trade relies on healthy plants to flourish. However, its very nature means that it is also a key pathway for the introduction and spread of plant pests and diseases. These pests and diseases threaten horticultural stakeholders, and can also cause huge ecological and economic damage. A horticultural sector accreditation scheme, underpinned by best biosecurity practice, could help reduce these threats. Drawing on survey responses, this study examines the plant‐buying habits of UK consumers and their appetite for a horticulture accreditation scheme. We consider the necessary scope of such a scheme and outline how it could be made appealing to the plant‐buying public.